Development of Didactical Design in Volume Teaching: Efforts to Improve Critical Thinking Abilities - Akbar, Ady; Herman, Tatang; Suryadi, Didi; Haruna, Nana Harlina (Jurnal Pedagogi dan Inovasi Pendidikan, 2025)
This study aims to identify and analyze the learning obstacles experienced by students in volume instruction in grade 5 elementary school, as well as to design didactical interventions that can enhance students' critical thinking skills. The study uses the Didactical Design Research (DDR) approach, focusing on the first stage, which is analyzing the didactical situation before teaching. The findings show a complex interaction between three types of learning obstacles: ontogenic, didactic, and epistemological. Ontogenic obstacles are related to individual students' cognitive development, didactic obstacles are linked to the teaching methods used, and epistemological obstacles arise when students struggle to understand abstract concepts. The study found that didactic obstacles often exacerbate ontogenic and epistemological obstacles. Based on these findings, a didactical design was developed using the framework of Didactical Situations Theory (TDS), which aims to create learning situations that allow students to build understanding through interaction with challenging yet accessible materials. Future research is expected to proceed to the stages of meta-pedagogical and retrospective analysis to evaluate the effectiveness of the developed didactical design in real-world learning contexts.